Widespread Use of Migratory Megafauna for Aquatic Wild Meat in the Tropics and Subtropics - Ingram, Daniel J.; Prideaux, Margi; Hodgins, Nicola K.; Frisch-Nwakanma, Heidrun; Avila, Isabel C.; Collins, Tim; Cosentino, Mel; Keith-Diagne, Lucy W.; Marsh, Helene; Shirley, Matthew H.; Van Waerebeek, Koen; Djondo, Maximin K.; et al. (Frontiers in Marine Science, 2022)
Wild animals are captured or taken opportunistically, and the meat, body parts, and/or eggs are consumed for local subsistence or used for traditional purposes to some extent across most of the world, particularly in the tropics and subtropics. The consumption of aquatic animals is widespread, has sometimes been sustained for millennia, and can be an important source of nutrition, income and cultural identity to communities. Yet economic opportunities to exploit wildlife at higher levels have definitively led to unsustainable exploitation of those same species. Over the past few decades, a vast literature has amassed on the harvest of wild-caught fish and terrestrial animals, but there has been comparatively less focus on the exploitation of aquatic non-fish animals for food and other purposes. Consequently, understanding the scope and potential threat of aquatic wild meat exploitation is an important first step towards appropriate inclusion on the international policy and conservation management agenda. Here, we present an overview of the contemporary use of aquatic megafauna (cetaceans, sirenians, chelonians, and crocodylians) in the global tropics and subtropics, for species listed on the Appendices of the Convention on the Conservation of Migratory Species of Wild Animals (CMS). We summarise available information, identify hotspots of exploitation, consumption, and trade of these migratory megafauna, and then discuss implications for the survival of the species affected and for human health. Finally, we provide recommendations for CMS in the context of the mandate of the Aquatic Wild Meat Working Group.